Effect of a12-month resistance training and aerobic training in abdominal adipose tissue and metabolic variables in patients with pre-diabetes: a randomized controlled trial (有氧和抗阻运动对糖尿病前期人群腹部脂肪和代谢指标的影响) - ZHOU Qianqian (周倩倩); LOU Qingqing (楼青青); YAN Juan (严娟); FENG Jitao (冯纪涛); YAO Jinlan (姚金兰); LIU Xiaorong (刘晓蓉) (中西医结合护理)
Objective To investigate the effects of resistance exercise and aerobic exercise on abdominal adipose tissue and metabolic indexes in adults with pre-diabetes. Methods From May 2014 to April 2015, 105 patients with pre-diabetes were randomly divided into aerobic exercise group (AT, n=35), resistance exercise group (RT, n=35) and control group (n=35). Patients in the intervention group completed aerobic exercise and resistance exercise for 12 months, control group maintained the original lifestyle without exercise intervention. Relevant indicators were measured at the time of enrollment and 12 months of intervention. The main outcome indicators were visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) measured by computed tomography (CT). The secondary outcome indicators were body composition, lipid distribution and metabolic variables. Results A total of 93 participants completed the study. There was no significant difference between the groups before intervention (P>0. 05). After intervention, the VAT of AT and RT was significantly lower than that of control group (P=0. 001, P=0. 014, respectively). Although there was no significant difference in SAT between different groups, the SAT in each exercise group decreased significantly over time (P=0. 001). The increase of muscle mass in RT was higher than that in AT and control group (P=0. 031, P=0. 045, respectively). Compared with control group, fasting plasma glucose (FPG) of AT and RT was significantly decreased (P=0. 014, P=0. 003, respectively). Conclusion Both aerobic exercise and resistance exercise can significantly reduce the abdominal fat content and FPG among patients with pre-diabetes. In addition, the effect of resistance exercise on increasing muscle mass is more remarkable. (目的 探讨抗阻运动与有氧运动对成人糖尿病前期人群腹部脂肪和代谢指标的影响。方法 选取2014年5月—2015年4月期间在江苏省中西医结合医院及丹阳市人民医院就诊的糖尿病前期患者105例, 随机分为有氧运动组(AT, n=35), 抗阻运动组(RT, n=35)和对照组(n=35)。AT组进行12个月的有氧运动干预, RT组进行12个月的抗阻运动干预, 对照组常规干预。观察入组时和干预12个月后人体成分和代谢指标, 使用计算机断层扫描(CT)测量腹部和内脏脂肪(VAT)和皮下脂肪(SAT)。结果 干预后AT组和RT组VAT较对照组显著降低(P=0. 001, P=0. 014)。AT组和RT组SAT显著下降(P＜0. 05)。RT组肌肉量增加高于AT组和对照组(P=0. 031, P=0. 045)。与对照组比较, AT组和RT组空腹血糖(FPG)明显降低(P=0. 014, P=0. 003)。结论 抗阻运动和有氧运动均能有效减少糖尿病前期人群的VAT和FPG水平, 抗阻运动增加肌肉量的效果更加显著。)